A GENDER-PERSPECTIVE EMPOWERMENT AND STRENGTHENING MODEL IN TTU DISTRICT BY YABIKU - ADEODATA LANIRIA CHARLA BARROS MBIRI; M. Angela Merici Siba; Fridus Bria (Universitas Wijaya Kusuma Surabaya, 2026)
This study examines the